ECM stiffness-tuned exosomes drive breast cancer motility through thrombospondin-1. (December 2021) - Patwardhan, Sejal; Mahadik, Pratiksha; Shetty, Omshree; Sen, Shamik
Abstract: Breast cancer progression features ECM stiffening due to excess deposition and crosslinking of collagen, which dramatically influence tumor behaviour and fate. The mechanisms by which extracellular matrix (ECM) stiffening drives breast cancer invasion is an area of active research. Here we demonstrate the role of exosomes in ECM stiffness triggered breast cancer invasiveness. Using stiffness tuneable hydrogel ECM scaffolds, we show that stiff ECMs promote exosome secretion in a YAP/TAZ pathway-dependent manner. Interestingly, blocking exosome synthesis and secretion by GW4869 abrogated stiffness regulated motility and contractility in breast cancer cells. Reciprocally, exogenous addition of ECM stiffness-tuned exosomes orchestrated a series of changes in cell morphology, adhesion, protrusion dynamics resulting in fostered cell motility and invasion. Proteomic analysis of exosomal lysates followed by overrepresentation analysis and interactome studies revealed enrichment of cell adhesion and cell migration proteins in exosomes from stiff ECM cultures compared to that of soft ones. Quantitative proteomics of exosomes combined with genomic analysis of human breast tumor tissues (TCGA database) identified thrombospondin-1 (THBS1) as a prospective regulator of stiffness-dependent cancer invasion. Knockdown studies confirmed that the pro-invasive effects of stiffness-tuned exosomes are fuelled by exosomal THBS1. We further demonstrated that exosomal THBS1 mediates these stiffness-induced effects by engaging matrix metalloproteinase and focal adhesion kinase. Our studies establish the pivotal role of exosomal communication in ECM stiffness dependent cell migration with exosomal THBS1 as a master regulator of cancer invasion, which can be further exploited as a potential theranostic for improved breast cancer management.